ON (NON-STANDARD) PSEUDO-VALUATIONS ON JU-ALGEBRAS - Romano, Daniel Abraham (Matematichki Bilten, 2025)
JU-algebra, as a generalization of KU-algebra, is the subject of study by several researchers in the second decade of this century. In addition to the previous one, the concept of pseudo-valuations on such algebras, generated by the ideal was introduced in 2019. This paper, as a continuation of previous research, refers to the design of the congruence relation on such an algebra  and the analysis of its properties induced by a pseudo-valuation on it. Also, three important properties of the JU-algebra quotient structure created in this way are proved.
Keywords: KU-algebra; JU-algebra; JU-ideal; JU-filter; standard pseudo-valuations; non-standard pseudo-valuation; congruence on JU-algebra by pseudo-valuation